Trend of Development of Forestry in Haldwani, Ramnagar and T & B Divisions of Uttar Pradesh during the last 50 Years - Sen, N. N. (Indian Forester, 1965)
Progress of silvicultural treatment for obtaining natural regeneration in Champion's B3 and A2 types of sal forests in Haldwani, Ramnagar and Tarai and Bhabhar Divisions of the U.P. forests in successive stages have been described. Success obtained in under planting with teak and replacement of understocked forests of these types by teak has been indicated and future programme given. The progress made up-to-date in artificial regeneration of the forests of miscellaneous species by more valuable species has been shown and the future programme indicated. The technique of large scale mechanised plantations of quick growing species has been described, the cost of formation indicated and a list of machinery and equipment maintained is given. The nursery practice for raising planting stocks of Eucalyptus hybrid has been described and the future programme of plantation given. Natural regeneration of sal in Champion's B3 type of forest.